Reducing Vulnerability to Climate Change in the Arctic: The Case of Nunavut, Canada - Ford, J D; Pearce, T; Smit, B; Wandel, J; Allurut, M; Shappa, K; Ittusujurat, H; Qrunnut, K (Arctic Institute of North America, 2007)
Research conducted with the communities of Arctic Bay and Igloolik in Nunavut identified key areas where policy can help Inuit reduce their vulnerability to climate change, focusing on the renewable resource harvesting sector. The policy responses are based on an understanding of policy development and decision making and on an understanding of the processes that shape vulnerability, which in Nunavut comprise the erosion of traditional Inuit knowledge and land-based skills, the weakening of social networks, and a reduction in harvesting flexibility. Policies relating to cultural preservation, wildlife comanagement, and harvester support can serve as entry points for influencing these processes. Our recommendations fall within the mandates of the Government of Nunavut and the institutions created under the Nunavut Land Claims Agreement, and they have been identified as policy priorities by communities and Inuit organizations.